PROSEDUR AUDIT ATAS UTANG USAHA PADA PT JKL OLEH KAP JEPTHA, NASIB DAN JUNIHOL - Eka Koamalasari, (2020)
This Final Project Report discusses the audit procedures for PT JKL trade payables engaged in ICT services. Services that provide infrastructure for IT. Accounts payable are an important enough account in the financial statements, and to ensure whether the trade payables are presented fairly. The auditor also conducts program audits based on the provisions of the Jeptha, Nasib and Junihol Public Accountant Firms. It can be concluded that the account of accounts payable at PT JKL was not found to be misstated so that it has been presented fairly in all material respects in accordance with accounting standards in force in Indonesia.